Is there a connection between immunohistochemical markers and grading of lung cancer with apparent diffusion coefficient (ADC) and standardised uptake values (SUV) of hybrid 18F‐FDG‐PET/MRI?. Issue 6 (24th July 2020) - Martin, Ole; Bruckmann, Nils‐Martin; Kirchner, Julian; Ullrich, Tim; Ingenwerth, Marc; Bogner, Simon; Eze, Chukwuka; Nensa, Felix; Herrmann, Ken; Umutlu, Lale; Antoch, Gerald; Sawicki, Lino M
Abstract: Introduction: To correlate tumour grading and prognostic immunohistochemical markers of lung cancer with simultaneously acquired standardised uptake values (SUV) and apparent diffusion coefficient (ADC) derived from hybrid PET/MRI. Methods: In this retrospective study, 55 consecutive patients (mean age 62.5 ± 9.2 years) with therapy‐naïve, histologically proven lung cancer were included. All patients underwent whole‐body PET/MRI using 18F‐flourdeoxyglucose (18F‐FDG) as a radiotracer. Diffusion‐weighted imaging of the chest (DWI, b‐values: 0, 500, 1000 s/mm 2 ) was performed simultaneously with PET acquisition. Histopathological tumour grading was available in 43/55 patients. In 15/55 patients, immunohistochemical markers, that is, phospho‐AKT Ser473 (pAKTS473), phosphorylated extracellular signal‐regulated kinase (pERK), phosphatase and tensin homolog (PTEN), and human epidermal growth factor receptor 2 (erbB2) were available. Results: The average SUVmax, SUVmean, ADCmin and ADCmean in lung cancer primaries were 12.6 ± 5.9, 7.7 ± 4.6, 569.9 ± 96.1 s/mm 2 and 825.8 ± 93.2 s/mm 2, respectively. We found a significant inverse correlation between the ADCmin and SUVmax ( r = −0.58, P < 0.001) as well as between the ADCmin and SUVmean ( r = −0.44, P < 0.001). Tumour grading showed a significant positive correlation with SUVmax and SUVmean ( R = 0.34 and R = 0.31, both P < 0.05) and a significant inverse correlation with ADCmin and ADCmean ( r = −0.30 and r = −0.40, both P < 0.05). In addition, erbB2 showed a significant inverse correlation with SUVmax and SUVmean ( r = −0.50 and r = −0.49, both P < 0.05). The other immunohistochemical markers did not show any significant correlation. Conclusion: 18F‐FDG‐PET/MRI showed weak to moderate correlations between SUV, ADC, tumour grading and erbB2‐expression of lung cancer. Hence, 18F‐FDG‐PET/MRI may, to some extent, offer complementary information to the histopathology of lung cancer, for the evaluation of tumour aggressiveness and treatment response.